Developing tools to promote culturally competent compassion, courage, and intercultural communication in healthcare. Issue 1 (December 2016) - Papadopoulos, Irena; Shea, Sue; Taylor, Georgina; Pezzella, Alfonso; Foley, Laura
Abstract Background Compassion is an important concept in healthcare, and in addition, care should be delivered in a culturally competent manner, taking into account the values, culture, and health beliefs of the individual. However, the training of nurses and other healthcare professionals may not adequately equip them to practice in a manner which is both compassionate and culturally competent. In this paper, we report on the development of three learning tools, designed to promote the skills and strengthen the capacity of nurses and healthcare professionals to provide culturally competent and compassionate care. Methods The project involved the participation of six European countries in the development of three learning tools, covering culturally competent compassion, culturally competent courage, and intercultural communication. The principles which informed the methodology derive from the previous work on the Papadopoulos, Tilki and Taylor (PTT) model of transcultural nursing and cultural competence, and were also informed by the Intercultural Education of Nurses in Europe (IENE1 & IENE2) projects. Each partner country was required to produce one tool for each topic area, based on guidance provided by the project co-ordinator, leading to the development of eighteen tools in total. The tools were administered mainly to student nurses to test their feasibility. Results The emerging tools contained important theoretical and practical components, whereby innovative learning methods and case studies were included. Student nurses enjoyed using the tools, and enjoyed their flexibility. The learning tools enabled students to become stimulated and to engage together leading to a positive learning experience. Discussion The tools allow for a positive learning experience and reflection of good practice to take place. The flexibility and content of the tools allows for them to be of equal value to other healthcare professionals as well as nursing staff. Conclusion The tools were initially utilised mainly with student nurses and were received with a positive response. Work is now in place to further implement the tools and evaluate the longer term effects among a range of healthcare professionals and service user health outcomes.